FACTORS OF STRENGTHENING THE IDEOLOGICAL IMMUNITY OF YOUTH IN THE PROCESS OF THEIR IDEOLOGICAL EDUCATION (Western European Journal of Historical Events and Social Science, 2025)
This article explores the essential factors that contribute to strengthening the ideological immunity of young people in the process of ideological education. The study emphasizes the importance of developing independent thinking, national consciousness, and resistance to destructive ideological influences among the youth. It analyzes the role of education, family, mass media, and social institutions in shaping a healthy worldview and ensuring spiritual and moral stability. The author also highlights the necessity of creating an effective system of ideological upbringing aimed at nurturing patriotic, enlightened, and socially active young generations